Isolation and characterization of 12 microsatellite loci in soapbark, Quillaja saponaria (Quillajaceae)1. (11th May 2015) - Letelier, Luis; Harvey, Nick; Valderrama, Aly; Stoll, Alexandra; González‐Rodríguez, Antonio
Abstract : Premise of the study: Microsatellite primers were developed for the endemic Chilean tree Quillaja saponaria (Quillajaceae), a common member of the sclerophyllous Mediterranean forest, to investigate intraspecific patterns of genetic diversity and structure. Methods and Results: Using an enriched library, 12 polymorphic microsatellite loci were developed in Q. saponaria . All loci consisted of dinucleotide repeats. The average number of alleles per locus was 5.3 (2–13), with a total of 64 alleles recorded in 39 individuals from three populations. Conclusions: The microsatellite markers described here are the first characterized for Q. saponaria . The polymorphic loci will be useful in studies of genetic diversity and genetic population differentiation in natural populations of this species.